2017
DOI: 10.1002/ajcp.12143
|View full text |Cite
|
Sign up to set email alerts
|

Applying a Social Justice Lens to Youth Mentoring: A Review of the Literature and Recommendations for Practice

Abstract: Youth mentoring interventions are often designed with the intention of promoting improved outcomes among marginalized youth. Despite their promise to reduce inequality through the provision of novel opportunities and increased social capital to marginalized youth, youth mentoring interventions hold the potential to reproduce rather than reduce inequality. In the current review, we explore literature on youth mentoring that has incorporated a social justice lens. We conclude that there is a need for greater att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
88
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(104 citation statements)
references
References 102 publications
2
88
0
Order By: Relevance
“…Prior recommendations for social justice frameworks in youth mentoring (Albright et al., ; Weiston‐Serdan, ) highlight the need to support adults to better understand systemic factors influencing the youth with whom they work. This study explored whether social justice trainings play a role in increasing mentors’ cultural competence and racial self‐efficacy, and whether these increases varied by participant shared identity with youth.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Prior recommendations for social justice frameworks in youth mentoring (Albright et al., ; Weiston‐Serdan, ) highlight the need to support adults to better understand systemic factors influencing the youth with whom they work. This study explored whether social justice trainings play a role in increasing mentors’ cultural competence and racial self‐efficacy, and whether these increases varied by participant shared identity with youth.…”
Section: Discussionmentioning
confidence: 99%
“…The pattern of findings from both studies that indicated significantly higher cultural sensitivity suggests that trainings may play a role in facilitating how mentors develop empathy for the environmental factors influencing youth. Increased understanding of the contextual factors in mentees’ lives is an important factor in understanding the systemic oppression that marginalized youth face (Albright et al., ). Moreover, this is an important prerequisite to future action.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Traditional one‐to‐one mentoring programs locate problems (i.e., a lack of role models for at‐risk youth) and solutions (i.e., deployment of middle‐class volunteers) at the individual, rather than societal, level (Schwartz & Rhodes, ). Although mentoring researchers and practitioners are beginning to attend to multiple levels of the social ecology, this individualistic ideology is still influential and may continue to drive some conservatives’ support for mentoring (Albright, Hurd, & Hussain, ). Conservatives may see mentoring as a way of addressing inequality by helping young people “pull themselves up by their bootstraps,” rather than increasing government spending on welfare, universal healthcare, and higher education (Schwartz & Rhodes, ).…”
Section: Political Ideology Religiosity and Support For Mentoringmentioning
confidence: 99%